Financing Management in Improving the Quality of Islamic Educational Institutions - Robiatul Andawiyah; Hamdani; Maimun (al-Afkar, Journal For Islamic Studies, 2025)
Every Islamic educational institution has the same target to achieve national education standards (SNP). The quality of education is important and is taken into account because of institutional demands so that these achievements can be recognized at the national level. One effort that can be made by education providers is to manage and utilize the finances obtained by Islamic education institutions so that they can be allocated to the needs of improving the quality of the institution. The aim of this research is to examine the financing management part in order to improve the quality of Islamic education institutions. This research can be useful as a reference for Islamic educational institutions in reviewing income, expenditure and allocation to fulfill education quality standards through management methods.